2016
DOI: 10.1016/j.cmi.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in the aetiology of prosthetic joint infections: a multicentre cohort study

Abstract: It is important to know the spectrum of the microbial aetiology of prosthetic joint infections (PJIs) to guide empiric treatment and establish antimicrobial prophylaxis in joint replacements. There are no available data based on large contemporary patient cohorts. We sought to characterize the causative pathogens of PJIs and to evaluate trends in the microbial aetiology. We hypothesized that the frequency of antimicrobial-resistant organisms in PJIs has increased in the recent years. We performed a cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
139
5
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(158 citation statements)
references
References 43 publications
8
139
5
6
Order By: Relevance
“…When we compared patients who were treated surgically due to PJI for the first time with patients who had already undergone at least one revision due to PJI, we found that S. epidermidis infections increased in the latter group. Contrary to data by others, Gram-negative bacteria were only rarely detected in our cases of prosthetic joint infection [19]. …”
Section: Discussioncontrasting
confidence: 99%
“…When we compared patients who were treated surgically due to PJI for the first time with patients who had already undergone at least one revision due to PJI, we found that S. epidermidis infections increased in the latter group. Contrary to data by others, Gram-negative bacteria were only rarely detected in our cases of prosthetic joint infection [19]. …”
Section: Discussioncontrasting
confidence: 99%
“…The most frequently used antibiotics for loading on titanium nanostructures are gentamicin and vancomycin; though others such as penicillin and streptomycin and antimicrobials like peptides or hydroxypropyltrimethyl ammonium have been used. The use of antibiotic monotherapy has been associated with bacterial antibiotic‐resistant emergence, and dual antibiotic therapy may prevent antibiotic‐resistance in local therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Though prosthetic joint infection (PJI) occurs infrequently (1‐2% of all cases), it is a nonetheless devastating, due to the high associated morbidity and substantial costs of this complication; indeed, the economic burden of PJI is expected to grow in the coming years with the increase in the number of patients undergoing arthroplasty replacements . The most frequently isolated microorganisms from these infections are Gram‐positive cocci, which represent up to 77% of all infections, the most common of which are Staphylococcus aureus and Staphylococcus epidermidis . After arthroplasty, systemic and prophylactic treatments of PJIs may be ineffective as antibiotics cannot easily reach the prosthesis–tissue interface, particularly if necrotic or avascular tissue remains after surgery; and increases in the antibiotic dose are associated with organ toxicity .…”
mentioning
confidence: 99%
“…Diagnosis within the first 2 weeks could enable rapid treatment before formation of resistant biofilms [2,16]. However, chronic infections can be "silent" or culture negative to conventional tests [4], and many patients with immune deficiency do not present with typical symptoms such as fever or elevated neutrophil counts [28], so their pain may be incorrectly attributed to aseptic loosening, instability, or malalignment.…”
Section: Introductionmentioning
confidence: 99%